Trade and dietary diversity in Eastern Europe and Central Asia - Ekaterina Krivonos; Lena Kuhn (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2019)
In public and academic debates, the linkages between agricultural markets and nutrition across the world are vividly discussed. This paper contributes to the ongoing debate by analyzing the relationship between greater openness to trade and dietary diversity. It focuses on the post-communist countries of Eastern Europe and Central Asia where trade reforms as part of the economic and political transition provide a natural experiment for studying the effects of trade openness on agricultural markets and consumer behaviour. Reduction in trade barriers, for instance in the context of the accession to the WTO and the EU, and the gradual integration with world markets after 1991 had implications for diets through changes in production, prices and incomes. We utilize country-level panel data for 26 post-communist countries in the period 1996-2013 to assess the effects of trade costs, openness to trade and incomes on dietary diversity measured by the Shannon entropy index. The results arising from fixed effects and instrumental variables estimation are consistent with previous findings that income growth affects dietary diversity positively and provide novel evidence that trade barriers reduce variety of products available in domestic markets, in particular fruits and vegetables.
urn:nbn:de:gbv:3:2-107194
Keywords: D12; F13; F68; Q11; Q18; 330; trade; nutrition transition; dietary diversity; post-communist countries; Eastern Europe